Can a heat-and-moisture exchanger attenuate inflammatory responses to exercise in sub-zero conditions? - Hanstock, H. G.; Tutt, A. S.; Persson, H.; Andersson, E. P.; Ainegren, M.; Stenfors, N. (British Journal of Sports Medicine, 2021)
Background Heavy endurance training in sub-zero environments increases risk of exercise-induced asthma. Heat-and-moisture exchangers (HME) can prevent exercise-induced bronchoconstriction but it is not known whether they protect against inflammatory responses to exercise in healthy individuals.